Evaluation of patient immunocompetence for immune checkpoint inhibitor therapy using the psoas muscle index: a retrospective cohort study - Tsurui, Toshiaki; Hamada, Kazuyuki; Mura, Emiko; Suzuki, Risako; Iriguchi, Nana; Ishiguro, Tomoyuki; Hirasawa, Yuya; Ohkuma, Ryotaro; Shimokawa, Masahiro; Ariizumi, Hirotsugu; Kubota, Yutaro; Horiike, Atsushi; et al. (Frontiers in Oncology, 2025)
IntroductionIn patients with cancer, sarcopenia is an indicator of poor prognosis and is associated with an increased risk of chemotherapy-related adverse events. Skeletal muscle interacts with the immune system, and sarcopenia is associated with immune senescence. However, the association between sarcopenia and the response to immune checkpoint inhibitor (ICI) therapy remains unclear.MethodsThis retrospective study included patients with advanced or recurrent non-small cell lung cancer treated with nivolumab or pembrolizumab monotherapy. The association between the psoas muscle index (PMI) and both clinical response and immune-related adverse events (irAEs) was assessed using logistic regression. The PMI was calculated as the cross-sectional area of the psoas muscle divided by the square of the height based on computed tomography scans performed before the initial administration of ICI therapy.ResultsA total of 67 patients were included in the analysis. Logistic regression analysis showed that PMI was associated with the overall response (odds ratio [OR]: 1.52; 95% confidence interval [CI]: 1.04–2.22; p = 0.030) and the risk of severe irAEs (OR: 1.72; 95% CI: 1.05–2.80; p = 0.031).ConclusionThese findings suggest that PMI is both an indicator of prognosis and a surrogate marker of immunocompetence in predicting the clinical response to ICI therapy.